The Performance Ethic of Counselors: Discrepancy Evaluation Model (DEM) Analysis - Pratiwi, Awalya Siska; Nuha, Moch. Syihabudin (Bisma The Journal of Counseling, 2025)
The Inadequacy Evaluation Model Analysis shows several significant gaps between expected standards and the actual implementation of guidance and counseling services in schools. These include incomplete needs assessments, unplanned service topics, limited time allocation for service delivery, an imbalance in the counselor-to-student ratio, inadequate counseling room facilities, unstructured service evaluations, the absence of formal evaluation reports, and counselors being assigned additional roles outside their core responsibilities. These findings highlight the urgent need for systemic improvements, including better planning, resource allocation, role clarification, and institutional support to enhance the effectiveness of guidance and counseling programs in schools. The Discrepancy Evaluation Model Analysis revealed several significant gaps between expected standards and the actual implementation of guidance and counseling services in schools. These include incomplete needs assessments, unplanned service topics, limited time allocation for service delivery, an imbalance in the counselor-to-student ratio, inadequate counseling room facilities, unstructured service evaluations, the absence of formal evaluation reports, and counselors being assigned additional roles beyond their core duties. These findings highlight the urgent need for systemic improvements, including better planning, resource allocation, role clarification, and institutional support to enhance the effectiveness of guidance and counseling programs in schools.